KODE BUDAYA DALAM NASKAH DRAMA SANG MANDOR KARYA RAHMAN ARGE TINJAUAN SEMIOTIKA ROLAND BARTHES - Dirmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to uncover and describe the cultural code system contained in Rahman Arge's drama script Sang Mandor using Roland Barthes' semiotic approach. This study uses a qualitative descriptive method with a focus on the cultural codes that appear in the drama text. The research data are in the form of sentences that represent cultural codes, obtained from the drama script Sang Mandor published in January 1992. Data collection was carried out through reading, listening, inventorying, and careful recording of dialogues between characters. The results of the study indicate that the drama script Sang Mandor predominantly contains cultural codes that reflect social values ​​and the community's outlook on life. These codes not only function as elements that build the story, but also contain deep cultural meanings and are still relevant in people's lives today. Therefore, this study is expected to help readers and literature lovers in understanding the cultural messages implied in the drama script Sang Mandor. In addition, this study is also expected to be a reference for future researchers to study the same work with a different approach so that the meaning of the drama is more comprehensive.